2005
DOI: 10.1162/jeea.2005.3.2-3.322
|View full text |Cite
|
Sign up to set email alerts
|

Learning Trust

Abstract: We examine the effects of different forms of feedback information on the performance of markets that suffer from moral hazard problems due to sequential exchange. As orthodox theory would predict, we find that providing buyers with information about sellers' trading history boosts market performance. More surprisingly, this beneficial effect of incentives for reputation building is considerably enhanced if sellers, too, can observe other sellers' trading history. This suggests that two‐sided market transparenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 8 publications
1
25
0
1
Order By: Relevance
“…22 If the distance coefficient captures information frictions, and if the PowerSeller mechanism were to be effective, then we would expect a smaller distance coefficient for transactions undertaken by PowerSellers. 22 Bohnet et al (2005), using laboratory experiments, argued that an important ingredient of well-functioning markets prone to moral hazard is not only buyers learning about sellers but also sellers learning about other sellers. As predicted, we find that distance affects non-PowerSellers more.…”
Section: ] E B a Y A N D T H E D E A T H O F D I S T A N C Ementioning
confidence: 99%
See 1 more Smart Citation
“…22 If the distance coefficient captures information frictions, and if the PowerSeller mechanism were to be effective, then we would expect a smaller distance coefficient for transactions undertaken by PowerSellers. 22 Bohnet et al (2005), using laboratory experiments, argued that an important ingredient of well-functioning markets prone to moral hazard is not only buyers learning about sellers but also sellers learning about other sellers. As predicted, we find that distance affects non-PowerSellers more.…”
Section: ] E B a Y A N D T H E D E A T H O F D I S T A N C Ementioning
confidence: 99%
“…21 See eBay's website for more details here: http://pages.eBay.com/sellerinformation/sellingresources/ powerseller.html. 22 Bohnet et al (2005), using laboratory experiments, argued that an important ingredient of well-functioning markets prone to moral hazard is not only buyers learning about sellers but also sellers learning about other sellers. eBay's feedback mechanism could thus facilitate exchanges through both these mechanisms.…”
Section: ] E B a Y A N D T H E D E A T H O F D I S T A N C Ementioning
confidence: 99%
“…We have chosen the amount specified to be paid back in the case that E fulfils trust in a way that makes the pay‐offs asymmetric. Symmetric payments may encourage fulfilling trust for reasons of fairness, rather than because E does what is expected of her (for example see Bacharach et al (2001), Bohnet and Huck (2004) and Bohnet et al (2005)).…”
Section: Experimental Designmentioning
confidence: 99%
“…Fukuyama (1995), Knack and Keefer (1997), Zak and Knack (2001), Beugelsdijk et al . (2004) and Bohnet et al . (2005).…”
Section: Introductionmentioning
confidence: 96%
“…At the social level there is much evidence that trust between people reduces transaction costs, fosters cooperation and is hence important for economic and social development; see e.g. Fukuyama (1995), Knack and Keefer (1997), Zak and Knack (2001), Beugelsdijk et al (2004) and Bohnet et al (2005). Easterly and Levine (1997) showed that, in terms of an ethnolinguistic fractionalization index, the degree of ethnic diversity can explain much of the observed cross-country differences in pro-growth policies and political stability.…”
Section: Introductionmentioning
confidence: 99%